A Quantitative Study of Historical Consciousness among Primary School Teacher Education Students Studying History, with a Focus on Ethnic Identity - Wanda, Karina; Putra, Wiene Surya (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to examine the level of historical awareness among Indonesian university students, focusing on the differences between Malay and Batak students. Historical awareness was measured based on four main components: knowledge of historical events, understanding of historical research methodology, interpretation of historical events, and the perceived usefulness of history. The study involved students from two universities, namely Medan State University representing Malay students and Sumatera University representing Batak students. Data were collected through the administration of a history awareness test using an instrument in the form of multiple-choice questions that had been tested for validity and reliability to ensure the accuracy of the results. Data analysis was conducted by calculating the proportion of average historical awareness scores for each ethnic group. The results showed that Malay students had a higher level of historical awareness compared to Batak students. The T-test indicated that there was no statistically significant difference between the historical awareness of Malay and Minang students (df = 78, sig. value 0.198 > 0.05), suggesting that both groups had comparable levels of historical awareness. The findings provide new insights into how ethnic background influences university students' historical understanding. The results of this study are expected to serve as a basis for the development of a more inclusive and contextualized history education curriculum in Indonesia.